Physiological Responses of Pacific White Shrimp Litopenaeus vannamei to Temperature Fluctuation in Low-Salinity Water - Wang, Zhenlu; Qu, Yuexin; Yan, Muting; Li, Junyi; Zou, Jixing; Fan, Lanfen (Frontiers in Physiology, 2019)
Temperature is a significant environmental factor in aquaculture. To investigate the physiological responses during temperature fluctuation (28°C 13°C), experimental shrimps (Litopenaeus vannamei) were treated with gradual cooling from acclimation temperature (AT, 28°C) to 13°C with a cooling rate of 7.5°C /d and rose back to 28°C at the same rate after 13°C for 24h. Hepatopancreas histological changes, plasma metabolites concentrations, relative mRNA expression of unfolded protein response (UPR) pathway and apoptosis in hepatopancreas and hemocyte were investigated. The results showed that with the decline of temperature, the number and volume of the secretory cells in hepatopancreas increased significantly, tubule lumen appeared dilatation and epithelial cell layer became thinner. The contents of glucose (Glu) significant decreased to the minimum value in 13°C for 24h. The contents of triglyceride (TG), total cholesterol (TC) and total protein (TP) increased and reached the peak in 13°C for 24 h. Alkaline phosphatase (ALP) and alanine aminotransferase (ALT) activities in plasma reached the lowest and highest value in 13°C respectively. The expressions of all genes related to UPR and apoptosis in hepatopancreas and hemocytes were significant changed during the cooling process and reached the highest level in 13°C and 13°C for 24 h respectively. During re-warming stage, the histopathological symptoms got remission, each of the plasma metabolites concentrations and genes expressions returned to AT levels. These results revealed that Pacific white shrimp can adapt to a certain level of temperature fluctuation by self-regulation.